Dioscorea sphaeroidea (Dioscoreaceae), a threatened new species from the high-altitude grasslands of southeastern Brazil with wingless seeds - Couto, Ricardo Sousa; Lopes, Rosana Conrado; Braga, João Marcelo Alvarenga (Phytotaxa, 2014)
Dioscorea sphaeroidea is endemic to the high-altitude grasslands of the Serra dos Órgãos National Park located in southeastern Brazil. Based on the spheroid shape of its fruit and seed, i.e., not flattened or winged, this new species is morphologically unusual in the Dioscorea genus. Moreover, its unique morphology leaves this new species with no clear position in the infrageneric taxonomy of Dioscorea. Herein we present the morphological description of this species, including a discussion of its ecology and habitat, distribution, and preliminary risk of extinction assessment.